Determination of optimal technological conditions for the manufacture of semi-finished products from gooseberry fruit - O. V. Golub; O. K. Motovilov; N. V. Motovilova; N. I. Davydenko (Пищевые системы, 2024)
The quality of pureed berries products is determined by many factors. The purpose of the study was to determine the optimal technological conditions for the manufacture of semi-finished products from gooseberries, providing for the use of equipment with a rotary machine (MAG‑50) and ensuring the required quality characteristics. The objects of research were semi-finished products from gooseberries. The manufacturing technology involved high-temperature processing or the use of the rotary machine MAG‑50. The research methods were standard. It has been found that in order to obtain products with the required quality characteristics, the duration of processing in MAG‑50 had the greatest influence. The optimal technological conditions for the manufacture of products in MAG‑50 have been determined: processing for 14–20 minutes at a temperature of 59–65°C of at least 72% of fresh berries or 58–65°C of at least 66% of quick-frozen ones. It has been established that the technology involving the use of rotary machine MAG‑50, compared with the high-temperature one, made it possible to obtain products with a lower content of mesophilic aerobic and facultative anaerobic microorganisms, molds (by 97.7 and 69.8%, respectively), better appearance characteristics (by 1.7%), color, texture and odor (by 2.3%), taste and aftertaste (by 3.6%). The state of the raw materials had the greatest impact on the content of yeast in semi-finished products — products made from fresh berries contained 48.7% more of them on average than products from quick-frozen ones. Compared with the Senator variety, gooseberry fruits of the Pink 2 variety made it possible to obtain products with a high content of soluble solids, sugars, minerals and ascorbic acid (by 18.2, 58.9, 7.7 and 61.8%, respectively), less titrated acids and dietary fibers (by 21.2 and 20.3%, respectively). The study demonstrates the potential of obtaining semi-finished products from gooseberries, regardless of their variety and condition by using the technology involving the use of MAG‑50.